Why Doesn’t the United States Have National Health Insurance? The Political Role of the American Medical Association - Alsan, Marcella; Neberai, Yousra (Quarterly Journal of Economics, 2026)
This article examines how the American Medical Association (AMA) helped shape the development of the U.S. health insurance system in the critical period after World War II. Working with the political public relations firm Campaigns, Inc., the AMA launched a nationwide campaign to weaken support for national health insurance by framing it as “socialized medicine,” while simultaneously enrolling people in private health insurance plans to shift demand away from a public alternative. Drawing on newly assembled archival data, we find that greater exposure to the campaign explains about 20% of the rise in private health insurance enrollment and a comparable decline in public support for a national program. The campaign also appears to have influenced policy making through coordinated messaging, resolutions passed by civic organizations, congressional rhetoric, and political donations. These findings suggest that the rise of private health insurance in the United States was not solely due to macroeconomic forces or collective bargaining; rather, it was also enabled by a strategic, interest group–financed effort to shape citizen views and influence policy.